2020
DOI: 10.3906/kim-2003-41
|View full text |Cite
|
Sign up to set email alerts
|

An anthracene based fluorescent probe for the selective and sensitive detection of Chromium (III) ions in an aqueous medium and its practical application

Abstract: An anthracene based fluorescent probe, integrated with thiophene moiety, exhibited selective and sensitive detection of chromium (III) ions over other metal ions. Its synthesis was achieved by simple mixing of two commercially available compounds, 2-aminoanthracene, and 2-thiophenecarboxaldehyde, in onestep without the needed complex purification process. The probe molecule (ANT-Th) offered exceptional features such as "turn-on" fluorescence response, low detection limit (0.4 µM), and fast response time (<1 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Thus, the comparison of this research work with the previously reported papers is given in Table . The results of comparison clearly show that the previously reported thiophene-appended imine-conjugated small molecules do not show any emission spectrum until the metal ion was added. While we achieved in synthesizing fluorescent probe L2 with a quantum yield of 0.002939, it shows an enhanced emission upon addition of cadmium ions.…”
Section: Results and Discussionsupporting
confidence: 51%
“…Thus, the comparison of this research work with the previously reported papers is given in Table . The results of comparison clearly show that the previously reported thiophene-appended imine-conjugated small molecules do not show any emission spectrum until the metal ion was added. While we achieved in synthesizing fluorescent probe L2 with a quantum yield of 0.002939, it shows an enhanced emission upon addition of cadmium ions.…”
Section: Results and Discussionsupporting
confidence: 51%
“…To investigate the potential of probe 13 in practical applications, probe (10 µM) in CH 3 CN/HEPES solution (v/v 6:4) at pH 7 was introduced onto circular test papers. They did not exhibit emission at 366 nm under UV light in the absence of metal ions, while only Cr 3+ ions exhibited a green emission [ 41 ] by a “turn-on” response ( Scheme 12 ) , thereby making it an efficient tool for Cr 3+ detection.…”
Section: Thiophene Based Chemosensors For Detection Of Cationsmentioning
confidence: 99%
“…In recent years, the development of highly sensitive and selective chemosensors for the detection of metal ions and anions has been of special interest to many researchers [1][2][3][4]. Not only because of their importance in living systems, medicine, and the environment, but also because they play essential roles in biological, chemical, ecological, and endocrine systems [5][6][7][8]. These metal ions and anions are also related to diverse environmental issues and other health-related problems.…”
Section: Introductionmentioning
confidence: 99%